Clinical utility of combined contrast-enhanced ultrasound and intracavitary contrast-enhanced ultrasound in the percutaneous treatment of pyogenic liver abscess - Giampiero Francica (Exploration of Drug Science)
Aim: This study aimed to evaluate the utility of the combined use of contrast-enhanced ultrasound (CEUS) and intracavitary CEUS (IC-CEUS) with diluted SonoVue in the management of percutaneous treatment for pyogenic liver abscess (PLA). Methods: 36 patients (23 males, 13 females; mean age 64 ± 13.9 years) with 39 PLAs (mean size 7.6 ± 3.4 cm) were selected for percutaneous catheter drainage (PCD) and/or percutaneous needle aspiration (PNA). CEUS and IC-CEUS were employed during the interventional maneuver and follow-up during hospital stay in all cases. Results: 33 patients with 24 PLAs underwent PCD, 8 patients with 10 PLAs were treated with single or multiple PNA, and the combination of PCD and PNA was used in the remaining 5 cases. During the treatment planning phase, the combined use of CEUS and IC-CEUS affected therapeutic choices (e.g., drainage technique, additional therapeutic measures) in comparison with pre-operative imaging in 66.7% of patients. Throughout the follow-up period, CEUS and IC-CEUS facilitated monitoring of PLA evolution, providing crucial information, especially with IC-CEUS, on the optimal timing of catheter removal. No adverse events occurred after CEUS and IC-CEUS. Conclusions: The combination of CEUS and IC-CEUS proved to be a powerful and safe tool for tailoring US-guided percutaneous treatments to patients with PLA.